Cloak and dollar : a history of American secret intelligence - Jeffreys-Jones, Rhodri (Yale University Press, 2002)
"Rhodri Jeffreys-Jones here offers a history of American secret intelligence from the founding of the nation through the present day. Jeffreys-Jones chronicles the expansion of American secret intelligence from the 1790s, when George Washington set aside a discretionary fund for covert operations, to the beginning of the twenty-first century, when United States intelligence expenditure exceeds Russia's total defense budget."--Jacket.